Türk denizcilik eğitimi için sistem planlaması - Poyraz, Özkan (Fen Bilimleri Enstitüsü, 1995)
Denizyolu taşımacılığında rekabet etmenin en önemli koşulu, denizdeki etkinliklerin güvenilirliğini ve ekonomikliğini geliştirerek taşıma maliyetlerini azaltmaktır. Bu amaca ulaşmak için gemiadamlarının niteliksel özelliklerini geliştirmek, denizdeki verimliliklerini artırmak gerekmektedir. Bu çalışmada, Türkiye'deki Denizcilik Eğitim-Öğretim Sistemi, STCW-78 sözleşmesi, IMO Model Kursları, denizde güvenlik ilkeleri, eğitim bilminin genel kabulleri, Türk deniz iş dünyasının talep ve olanakları, işletme ve iktisat bilimlerinin ilkeleri ve modern teknolojinin gerekleri doğrultusunda incelenmiş, problemler ortaya konulmuştur. Çalışma sonunda, denizyolu taşımacılığının verimliliği ile denizcilik eğitim- öğretimi arasında çok yakın bir ilişki olduğu sonucuna varılmıştır. Ayrıca, Türk Denizcilik Eğitim-Öğretim Sisteminin geliştirilmesi için bir çözüm modeli önerilmiştir.

Over the last 25 years, it is observed that world shipping has undergone several significant technological and organizational changes [1]. It is widely acknowledged that the last decade has produced significant changes in the manning of ships and the organization of work on board. In particular, there have been major technological developments in shipboard equipment, which have greatly changed the nature of the work undertaken on board, the skills needed by today's seafarers and the number of seafarers required to man modern vessels. Although all of these technological developments provide greater efficiency and greater safety, it may be also said that adding more sophisticated equipment to the ships may be no avail If the people on those ships have no idea how to use this equipment. Therefore something should be done about better education for seafarers. According to the survey which has been carried out recently by P and I clubs in U.K., estimates reveal that 46% of all major claims are caused by shipborne personeli, Mr. William O 'Neil, Secretary General of the IMO, goes ever further, by estimating that up to 80% of seaborne accidents can be directly attributed to human error. The most important factor for competing in maritime transportation İs to reduce the transportation cost by increasing efficiency of maritime safety and economy.In order to achieve this task,it's needed to develop the productivity of the seaman by increasing the qualifications. Having indentified the principal cause as human error, we can easily understand the role of education and training establishments and safety management system alike. Maritime education and training encourages component integrated action and minimises the effect of potential hazards. The problem of maritime safety is global and affects the whole shipping economy. If world demand decreases for the carriage of goods by sea, this causes ship owners to economise as far as maritime safety is concerned where they find that they are subject to conditions of maximum productivity in a climate of perfect competition. Maritime safety is not yet seen by the industry as a fixed cost, inevitable when setting their profit margins. xn The shipping world is entering the final stage of reviewing the IMO Convention on Standards of Training,Certification and Watchkeeping (STCW).In it's new form,STCW is set to have profound influence on the manner in which the competence of personnel to perform tasks safely and effectively is assessed and assured over the next decade. Another standard put in maritime training is the IMO model courses which are prepared to achive a common standard in maritime safety and pollution prevention around the world. Each model course defines the scope of training, objectives and provides the basic teaching material to enable traninees to meet the objectives. Model courses are aimed at seagoing staff, maritime safety and pollution prevention administrator and shipping company staff.[l]. The international regulations adopted by IMO and ther international bodies should constitute the essentional base on which any sound methods of maritime education must be founded. [1] We are also witnessing the continuing development and installation of increasingly sophisticated maritime technology that demands high levels of knowledge and skill from on board personnel. If ships are to be operated safely and efficiently and public reassured that quality are being maintained.this new technology will itself require the new support of specalized trainning programmes. For IMO,the objectives of safer ships and cleaner oceans can only be achieved if the world wide maritime industry is prepared to establish standards of training that will meet the challange of modern technology[2]. There is a shortage of officers and ratings, in developing countries. As well as the quantity of the personnel needed to meet this shortfall, the quality of education also becomes very important [1]. Some trends are already apparent in Turkey. Many of the traditional Turkish coaster owners are now looking to move up the scale into the hadymax sector and a number of them have been active in secondhand markets. As the Turkish maritime fleet has expanded there has been an associated necessity to train more seafarers. So in this research study; the Turkish maritime education and training system will be examined in view of pedagogy and maritime transportation engineering needs in order to improve maritime safety and productivity and the total income and profit of the sector. This thesis will attempts to develop an optimal system o maritime education by taking into account revised international stardards, new technological developments and future trainings needs of the industry to assist determination of solution model and subsystems. The study covers;. a description of the problems of the current system of Turkish Maritime Education and Training. Xlll . an outline of national and international administrative organizations that affect such maritime educations and training,. a survey of the area of physical conditions and objectives of maritime educations and training,. a comparision of international regulations, codes, and recommendations, adopted by IMO, with national legal regimes.. the determination of a new national educational model of training programs and curricula that can be used at secondary and post secondary level to assist students of maritime education to learn more effectively and efficiently. In developing, this model, This thesis reached the following recommendations;. Turkish maritime training centers should use the IMO model courses and STCW conventions of 1978 as a frame of reference in desingning and conducting new marine training programes,. The National maritime education and training institutes should optimise the utilization of fellowship, training epuipment and educational schemes with the objective of enhancing effectiveness of training and education at low cost... Maritime education and training should be based on experience at sea and sandwich type courses,. In constrast to the remarkable increase in capacity of the Turkish Maritime Fleet, educational infrastructure in maritime education has remained relatively stagnant for a long time and therefore inadequate to meet the increasing demand for qualified officers in Turkey. For this reason, the number and capacity of officer schools should be increased, as well as implementing the educational standards required in order to meet the STCW-78 convention and IMO recommendations.. To achieve required standards in the maritime education process, curriculum frameworks should satisfy the following criteria; -Maximization number and quality of students in their transition from school to the world of work at sea, -Carrefully monitoring industrial trends and market needs of the shipping sector. -Ensuring skill competence and standards of performance -Taking into account the human element, -Implementation of "school to work" and "contextual" learning methods, xiv .. Maritime colleges and academies should be audited, impartially, according to international standards. Examiner should be trained for their work and be required to keep their knowledge in line with current practice and relevant professional experience. Maritime training centers should be equipped with modern training facilities, simulation and other electronic equipment, to meet the high level of tuition required. Although simulators have their uses for retraning and assessign seafarers and revalidating certificates, there is no substitude for actual sea training on board a ship under live conditons, Growth in the maritime sector as a whole also required more comprehensive training for shore based functions related to the industry, covering the whole range of ship management, agency, chartering, cargo handling, finance, public relations and so on. In this respect, Turkey should develop formal higher education and training for shorebased occupations. Shipping companies should consider introducing new training programmes aimed at senior ship managers and sea staff as a consequence of the benfits to be gained from a proper management within their operation. It should be recognised by Turkish Administration that the certificate structure embodies in the present national system assumes a traditional departmental organization and hierarchy of tasks, duties and responsibilities abroad ship and alternative job assignments are being developed within the shipping industry, giving rise to the need for a more flexible structure of certification. Considering developments in vocational and technical education, changes, in trainers roles, the demands of the world of work at sea, as well as vocational needs, appropriate process and programs for training should be developed and be continuously improved in the light of developments in maritime industry. The teaching staff at Tukish Maritime Institutes consists mostly of teachers that have no academic titles or experience in maritime industry. Due to this fact, Postgraduate Master and Doctor of Philosophy studies should be encouraged. There are also critical problems concerning maritime teachers, educational, social, economic, and employment condition. As a result of this problems, the status of maritime instructors is not socio-economically attractive. One of the main problems arises in relating academic theory to practice in the provision of the statutory sea service of the potential deck officer. The school credit assesment covering the industrial attachment needs to be fully recognized using the trainee officers personel experience log book as evidence of the continuing process during the time at sea. But there is no school ship in Turkey so that trainees have to serve on board a ordinary merchant vessel which the xv manning of the ship doesn't include a training officer from the college. It is important that the government should appropriate the resources for a training vessel.. New technological developments also provide increasing potential for the assessment of an individual's competence to perform the necessary skill in the workplace.A revolution in development of maritime training solfware is now underway. Most vessels today are equipped with computers. Computer aided learning is an effective method of accuiring knowledge,understanding and,in some cases,skill depending upon the degree of sophistication and interactive nature of the programming. Simulation modelling can readily be used with the powerful PC s of today to take reality on board[2]. In this work, Turkish Maritime Education and Training System is searched and problems are put forward in wiev of STCW 78 Convention,IMO Model Courses Principal of Maritime Safety,the demands and facilities of Turkish Maritime Bussiness. At the end of this work,it is shown that the quality of maritime education and training system affects the productivity of maritime transportation positively. In consideration of the surveys stated in the above paragraphs solution model for the problems of Turkish Maritime Education and Training System is structured.
A System planning for Turkish maritime education
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1995
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 1995
Keywords: Denizcilik eğitimi; Sistem planlama; Maritime education; System planning